Automated bank note identification system for visually impaired subjects in Malaysia - Funke Olanrewaju, Rashidah; Fajingbesi, Fawwaz Eniola; Mahmoud, Shaibo Mohammed M (IEEE, 2016)
Visually Impaired Malaysians find great difficulty in recognizing bank notes as there are no commercially available aid for her currency and not much research done in the area. A very low cost, high efficient system has been proposed to help visually impaired Malaysians identify her bank notes. This system is built around the unique color of her bank note. The system features a sound module, color sensor module and a microcontroller module. These three module offer the system a unique ability to identify Malaysian bank currency and produce audible sound of the currencies’ denomination. The efficiency of the proposed solution has been properly tested on a dataset composed of consecutive randomized banknotes including both positive images (Malaysian banknotes) and negative images (Non Malaysian banknotes and plain color notes) collected under a variety of conditions. The proposed algorithm, achieves overall efficiency of 94.17% recognition rate.